2012
DOI: 10.1108/03684921211213007
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a cybernetic epistemology: sequence learning systems

Abstract: Purpose -The purpose of this paper is to analyze how sequence learning can build on pattern-recognition systems and how it can contribute to the behavioral options of goal-oriented systems. Design/methodology/approach -A functional approach is used to develop the necessary cybernetic structures of a subsystem for sequence learning, that can recognize patterns, register patterns occurring repeatedly and connect these to sequences. Based on that it is analyzed how goal-oriented systems can use information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…So far we showed that ranging from feedback systems via various forms of adaptive systems to learning systems using pattern recognition and sequence learning (Nechansky, 2012c). Now here we found the continuation of this necessary evolution, showing how anticipation builds on sequence learning.…”
Section: A Necessary Evolution Of Cybernetic Structuresmentioning
confidence: 88%
See 2 more Smart Citations
“…So far we showed that ranging from feedback systems via various forms of adaptive systems to learning systems using pattern recognition and sequence learning (Nechansky, 2012c). Now here we found the continuation of this necessary evolution, showing how anticipation builds on sequence learning.…”
Section: A Necessary Evolution Of Cybernetic Structuresmentioning
confidence: 88%
“…As already mentioned we will consider here just temporal patterns connected via the "associative" way (Nechansky, 2012c). And we will only name some of the many internal controller functions, which enable this data processing.…”
Section: A Basic Structure For a Subsystem For Anticipationmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the decision problem where to the whole system should turn its attention (towards the pattern or the sequence). We concluded that a subsystem for attention directing emerges here as a cybernetic necessity (Nechansky, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers we analyzed the cybernetic structures of goal-orientated systems of increasing complexity, starting with feedback systems (Nechansky, 2006), via different forms of adaptive and learning systems (Nechansky, 2008(Nechansky, , 2009(Nechansky, , 2010a(Nechansky, , b, 2012a to sequence learning systems (Nechansky, 2012b). The overarching epistemological principle applied in all these investigations was that elementary decisions are goal-orientated acts following the form: if{ðdataÞ ðrelationÞ ðgoalÞ}; then {trigger for a goal -orientated action}:…”
Section: Introductionmentioning
confidence: 99%